Richard Linklater's Slacker - Daniel, Lee 1962-; Brennan, Meg; Basquez, Rudy; Caffeine, Jean; Hockey, Jan (<<The>> Criterion Coll., 2004)
Richard Linklater's Slacker presents a day in the life of a subculture of marginal, eccentric, and overeducated citizens in and around the University of Texas; a prescient look at an emerging generation of aggressive nonparticipants.
Bildformat: 1.33:1 aspect ratio. - New high-definition digital transfer, with restored image and sound supervised by director Richard Linklater and director of photography Lee Daniel, made from original 16 mm film elements
Orig.: USA 1991
Enth. three audio commentaries featuring Richard Linklater and members of the cast and crew ; casting tapes featuring select "auditions" from the over one-hundred-member cast, with an essay from production/casting director Anne Walter-McBay ; an early film treatment ; ten-minute trailer for a documentary about the landmark Austin café, L es Amis, which served as location for several scenes in "Slacker" ; stills gallery featuring hundreds of rare behind-the-scenes production and publicity photos ; "The roadmap", the working script of "Slacker", including fourteen deleted scenes and alternate takes ; footage from the "Slacker" tenth-anniversary reunion in Austin, Texas in 2001 ; "Slacker" cultural essay by Linklater ; information about the "Austin Film Society", founded in 1985 by Linklater with Daniel, including early flyers from screenings
Keywords: University of Texas -- Drama; Subculture -- Texas -- Austin -- Drama; Subkultur; Universität; Austin (Tex.) -- Drama; Austin, Tex.; Film; DVD-Video; Comedy films; Feature films; Video recordings for the hearing impaired